The Efficacy of Soleus Push-Up in Individuals with Prediabetes: A Pilot Study - Dávid Elek; Miklós Tóth; Balázs Sonkodi; Pongrác Ács; Gábor L. Kovács; Péter Tardi; Csaba Melczer (Sports)
Background/Objectives: Hamilton and colleagues invented the soleus push-up exercise and showed that this exercise method was successful in reducing postprandial blood glucose levels in sedentary individuals. The objective of the current pilot study was to assess the efficacy of the soleus push-up in individuals with prediabetes and to evaluate the feasibility of incorporating this exercise method into their daily routine. Methods: Ten participants (mean age: 53.3 ± 2.7 years; four females, six males) with prediabetes were included in the study. Initially, participants underwent an oral glucose tolerance test (OGTT) while being sedentary to establish baseline postprandial blood glucose measurements. During a subsequent OGTT, participants concurrently performed the soleus push-up (SPU) exercise either with or without electromyographic (EMG) feedback. Blood glucose levels were measured at 15 min intervals over the two-hour duration of both OGTTs. Results: We observed that performing the SPU in a sitting position during the oral glucose tolerance test resulted in approximately a 32% reduction in postprandial glucose excursion compared to the sedentary baseline results. This effect was also present in the absence of EMG feedback. Conclusions: Our findings suggest that this repetitive, prolonged contractile muscle activity can improve metabolic regulation in prediabetic individuals without the need for a laboratory setting. SPU may be a viable and effective exercise to support metabolic health in home or work environments. However, further validation is needed with a larger sample size.